The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1001/jamaneurol.2019.3762
|View full text |Cite
|
Sign up to set email alerts
|

Minocycline at 2 Different Dosages vs Placebo for Patients With Mild Alzheimer Disease

Abstract: ; for the Minocycline in Alzheimer Disease Efficacy (MADE) Trialist Group IMPORTANCE There are no disease-modifying treatments for Alzheimer disease (AD), the most common cause of dementia. Minocycline is anti-inflammatory, protects against the toxic effects of β-amyloid in vitro and in animal models of AD, and is a credible repurposed treatment candidate. OBJECTIVE To determine whether 24 months of minocycline treatment can modify cognitive and functional decline in patients with mild AD. DESIGN, SETTING, AND… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
99
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(108 citation statements)
references
References 32 publications
1
99
0
1
Order By: Relevance
“…In terms of the translatability of these finding, minocycline is currently under investigation as adjunctive therapy for Alzheimer's disease 68 , schizophrenia 69 and multiple sclerosis 70 with mixed results. While some studies report superiority over placebo, for instance in a metanalysis of adjunctive minocycline for schizophrenia 71 , others report little or no therapeutic benefit as well as issues of tolerability of a higher 400 mg dose 68 . Future work determining whether minocycline provides the same cognitive benefits to people with obesity as observed in these rodent studies, as well as investigations into long-term cognitive rescue, are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of the translatability of these finding, minocycline is currently under investigation as adjunctive therapy for Alzheimer's disease 68 , schizophrenia 69 and multiple sclerosis 70 with mixed results. While some studies report superiority over placebo, for instance in a metanalysis of adjunctive minocycline for schizophrenia 71 , others report little or no therapeutic benefit as well as issues of tolerability of a higher 400 mg dose 68 . Future work determining whether minocycline provides the same cognitive benefits to people with obesity as observed in these rodent studies, as well as investigations into long-term cognitive rescue, are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…However, findings about minocycline's effects in animal models of AD and TBI have been mixed, ranging from beneficial to harmful (Garwood et al , ; Ferretti et al , ; Yang et al , ; Scott et al , ). Minocycline also did not delay the progression of cognitive impairment in people with mild AD over a 2‐year period (Howard et al , ). These results suggest that more specific targets of microglia or astrocytes are required to alleviate cognitive impairment without also triggering side effects.…”
Section: Introductionmentioning
confidence: 99%
“…In humans, unfortunately, a recent randomized clinical trial reported that 24 months of minocycline treatment did not delay the progression of cognitive or functional impairment in patients with mild AD [106]. The authors speculated that the absence of clinical benefits in this trial could be ascribed to (i) the potentially lesser pathological significance of neuroinflammation in mild AD, (ii) potentially insufficient doses of minocycline to afford efficacy (of note, this agent would not result in apparent benefits even if higher doses were used, because of its tolerability), and (iii) potential clinical benefits that would be too small for detection [106]. In addition to minocycline, there is an emerging list of factors with therapeutic potential, including taxifolin [4,57], ω-3 polyunsaturated fatty acids [107,108], oxytocin [109,110], and exercise [111,112]; therefore, concurrent treatment might be beneficial, as suggested recently [113].…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Minocycline exerts inhibitory effects on microglial activation, thereby leading to neuroprotection and suppression of cognitive impairment in a mouse model of CAA [101,104] and AD [102,103,105]. In humans, unfortunately, a recent randomized clinical trial reported that 24 months of minocycline treatment did not delay the progression of cognitive or functional impairment in patients with mild AD [106]. The authors speculated that the absence of clinical benefits in this trial could be ascribed to (i) the potentially lesser pathological significance of neuroinflammation in mild AD, (ii) potentially insufficient doses of minocycline to afford efficacy (of note, this agent would not result in apparent benefits even if higher doses were used, because of its tolerability), and (iii) potential clinical benefits that would be too small for detection [106].…”
Section: Future Perspectivesmentioning
confidence: 99%